China English in Light of Skopos Theory (International Journal of Psychosocial Rehabilitation, 2020)
With the development of globalization and intercultural communications, the acceleration of China’s merging into the international society, and the spread of China English and its Chinese-colored expressions will unavoidably be widely accepted, suggesting that the study of China English is of great practical value. The concept of “China English” has aroused heated discussion, but the discussion only proves that the expressiveness of China English and its Chinese culture-loaded expressions will inevitably make it be accepted worldwide with the Chinese culture-loaded expressions translated into English. From the perspective of translation theories, a brief introduction to Skopos theory is given in this paper by analyzing the Skopos principle, coherence principle, and fidelity principle, as well as the adequacy principle in the framework of Skopos theory. Through detailed analysis of Chinese-English translation versions containing China English from cultural translation categorized into five aspects, namely, ecological culture, material culture, social culture, religious culture, and linguistic culture, which would be further demonstrated through specific translation examples from Gu Hua’s literary works---—Pagoda Ridge and Other Stories—the paper researches on China English in Chinese-English translation from the perspective of Skopos theory. Meanwhile, it is assumed that some mistranslated versions or Chinglish expressions, which proved to be expressive and useful in practical communication, may be transformed into China English, which is acceptable in the English world.